Bank diversification strategy and intellectual capital in Ghana: an empirical analysis - King Carl Tornam Duho; Joseph Mensah Onumah (Asian Journal of Accounting Research, 2019)
The purpose of this paper is to examine the impact of intellectual capital and its components on bank diversification choice.Both asset and income diversification are computed and an unbalanced panel data set of 32 banks covering the period 2000–2015 have been used. The panel corrected standard error regression has been used to account for serial correlation and heteroscedasticity.The study found that intellectual capital determines the choice of diversifying. Precisely, intellectual capital motivates asset diversity but it dissuades income diversification. Human capital and structural capital are major components that determine asset diversity decisions. Income diversification decision, in this case to choose a focus strategy, is determined by human capital. This gives credence for the human capital theory in Ghana. Competition encourages a focus strategy. Bank size and leverage enhances income diversification while stock exchange listing and government ownership fosters the focus strategy.Diversification strategy, knowledge base of staff, corporate governance and internal control have been considered as factors leading to the collapse of some Ghanaian banks in 2017–2018. The study provides relevant insights for regulators, decision support units and corporate boards. Intellectual capital and value added metrics should be used for modelling and decision making as they have value relevance.This is a premier study that has examined the nexus between diversification strategy and intellectual capital in banks.